Population pharmacokinetics of quinine in pregnant women with uncomplicated Plasmodium falciparum malaria in Uganda. - Kloprogge, F; Jullien, V; Piola, P; Dhorda, M; Muwanga, S; Nosten, F; Day, N; White, N; Guerin, P; Tarning, J (2014)
OBJECTIVES: Oral quinine is used for the treatment of uncomplicated malaria during pregnancy, but few pharmacokinetic data are available for this population. Previous studies have reported a substantial effect of malaria on the pharmacokinetics of quinine resulting from increased α-1-acid glycoprotein levels and decreased cytochrome P450 3A4 activity. The aim of this study was to investigate the pharmacokinetic properties of oral quinine in pregnant women with uncomplicated malaria in Uganda using a population approach. METHODS: Data from 22 women in the second and third trimesters of pregnancy with uncomplicated Plasmodium falciparum malaria were analysed. Patients received quinine sulphate (10 mg of salt/kg) three times daily (0, 8 and 16 h) for 7 days. Plasma samples were collected daily and at frequent intervals after the first and last doses. A population pharmacokinetic model for quinine was developed accounting for different disposition, absorption, error and covariate models. RESULTS: Parasitaemia, as a time-varying covariate affecting relative bioavailability, and body temperature on admission as a covariate on elimination clearance, explained the higher exposure to quinine during acute malaria compared with the convalescent phase. Neither the estimated gestational age nor the trimester influenced the pharmacokinetic properties of quinine significantly. CONCLUSIONS: A population model was developed that adequately characterized quinine pharmacokinetics in pregnant Ugandan women with acute malaria. Quinine exposure was lower than previously reported in patients who were not pregnant. The measurement of free quinine concentration will be necessary to determine the therapeutic relevance of these observations.